Athar al-Shi‘r fī Tadwīn al-Aḥdāth al-Tārīkhīyah fī al-Qarn al-Tāsi‘ ‘Ashar: Qaṣīdat al-Shaykh Muhammadu Bello ibn al-Shaykh Usman ibn Fodio fī Ghazwat Kano Unmūdhajān - Muhammad Safiyyu Abdul Kadir (Al-Ma‘rifah, 2020)
Poetry is a notable record for historical events, a tool for arousing enthusiasm and a capability of emotional expression that drives society. The objective of this article is to investigate and appraise the degree for special literary description on poetic influence in the recording of historical events in the 19th century in Nigeria. The article contains a biography of the poet Shaykh Muhammadu Bello bin Sheikh Usman bin Fodio and preamble that will assist in understanding the meaning of historical Arabic poetry. The theme of this article comprises the meaning of historical Arabic poetry, word expression, skills in the language of poetry, the poet’s artistic doctrine, and the belief of the poet feels. The poetry of historical events is counted among the best poems in Arabic literature of the past and present period. The author collected lots of data and will use the descriptive and analytical methods in carrying out the research.